International comparisons of energy consumption - Dunkerley, Joy.; Resources for the Future; Electric Power Research Institute (Washington, D.C. : Resources for the Future, 1978)
This workshop is one of a series of projects concerning international comparisons of energy consumption undertaken jointly by EPRI and RFF.
Proceedings of a workshop sponsored by Resources for the Future and the Electric Power Research Institute.
Includes bibliographical references.
II 15/01/2019
Loans
Keywords: Energy consumption; Energy policy